The Role of Resilience in Predicting the Care Burden of Family Caregivers of Stroke Patients: Descriptive Cross-Sectional Study - Sajjad Amiri Bonyad; Faezeh Shamlou Hasani; Arezou Karampourian; Behnaz Alafchi (نشریه پرستاری ایران, 2024)
Background & Aims The family caregivers of stroke patients experience a high care burden that has negative effects on their lives. Resilience is a factor that seems to be able to help them adapt to these conditions. The present study aims to determine the role of resilience in predicting the care burden of family caregivers of stroke patients. Materials & Methods In this descriptive-correlational study with a cross-sectional design, 194 family caregivers of stroke patients in Besat Hospital in Hamedan, Iran, in 2023 participated. The patients had moderate disability (A score of 61-90 based on the Barthel index). Participants were selected by a convenience sampling method. Data collection tools included a demographic form, Novak and Guest’s care burden inventory, and the Connor-Davidson resilience scale. Data analysis was done in SPSS software, version 25 using descriptive statistics, Pearson correlation test, and linear regression analysis. Results The age of caregivers was 42.53 years; 52% were male and 26.8% had a high school diploma. The mean scores of care burden and resilience were 86.35±13.09 and 42.56±10.38, respectively. The relationship between care burden and resilience was inverse and significant (P<0.05, r=-0.185). Resilience was found to be the predictor of care burden (β=-0.233). Conclusion Given that resilience is one of the effective factors in reducing the care burden of the family caregivers of stroke patients, it is recommended that health care providers, by identifying effective strategies, help caregivers of these patients to strengthen their resilience to reduce their care burden and help them in caring for their patients.